2018
DOI: 10.1111/bjd.17277
|View full text |Cite
|
Sign up to set email alerts
|

Sunscreen applied at ≥ 2 mg cm−2during a sunny holiday prevents erythema, a biomarker of ultraviolet radiation‐inducedDNAdamage and suppression of acquired immunity

Abstract: This summary relates to https://doi.Summary 在英国,皮肤癌发病率的增速比其他形式癌症更快。此病中致死性最强的形式为黑色素瘤皮肤癌,现在所影响 的人数比 28 年前增多了128%。已知防晒系数 (SPF) 在按 2 mg /cm 2 外用防晒霜时可以保护皮肤免于日晒 伤。但是,当在假期时,人们通常只外用 0.8 mg / cm 2 防晒霜 此研究旨在确定每天暴露于日光的假期中的通常 防晒霜使用是否会导致诸如日晒伤等皮肤癌风险因素。参与者们在 Tenerife 度过一周,Tenerife 是一个紫外线 指数非常高的地区。22 名参与者在无指导情况下自行使用他们的防晒霜,向 40 名参与者提供 SPF 15 防晒霜 和有效使用的指南(每天三次,2 mg /cm 2 )。发现遵守通常防晒霜使用方式的参与者中日晒伤和其他与皮肤癌 相关风险因素的水平显著高于遵守优化使用指南以达到 SPF 15 的参与者。遵守 SPF 15 防晒霜有效使用指南 的个体在 5 个身体暴露部位没有发生日晒伤。这项研究的结果强调了防晒霜的通常使用在大部分人群中不能 提供充分的日光防护。不仅如此,它还证实日晒… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 59 publications
(82 reference statements)
1
43
0
Order By: Relevance
“…Few investigations have reported the erythemal reaction due to UV radiations at low doses on human skin . The results for erythema level are in accordance with a recent investigation, though using alternate technique, which concludes the reduction in erythema level by using sunscreen .…”
Section: Discussionsupporting
confidence: 85%
“…Few investigations have reported the erythemal reaction due to UV radiations at low doses on human skin . The results for erythema level are in accordance with a recent investigation, though using alternate technique, which concludes the reduction in erythema level by using sunscreen .…”
Section: Discussionsupporting
confidence: 85%
“…Fuller details of all aspects apart from vitamin D status are described in Narbutt et al . As previously reported, all nonvitamin D parameters were normally distributed, as are pre‐ and postholiday 25(OH)D 3 and the differences between them. The addition of the 25(OH)D 2 data (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that sunscreen intervention in the same participants inhibited erythema. In contrast, there was marked erythema with discretionary sunscreen use …”
mentioning
confidence: 99%
“…Sunscreen protection varies according to the thickness and distribution of application, sun protection factor, and decay in effectiveness over time. Optimal sunscreen use (at 2 mg/cm 2 ) has been shown to prevent solar UVR immunosuppression, as measured by contact hypersensitivity responses (Narbutt et al, 2018). There is currently no validated method for correcting UVR exposure for sunscreen use based on questionnaire-derived data.…”
Section: Uvr and Response To Immunizationmentioning
confidence: 99%